Ocular Manifestations of Paediatric Inflammatory Bowel Disease: A Systematic Review and Meta-analysis. - Ottaviano, Giorgio; Salvatore, Silvia; Salvatoni, Alessandro; Martelossi, Stefano; Ventura, Alessandro; Naviglio, Samuele (J Crohns Colitis, 2018)
Background and Aims: Ocular extraintestinal manifestations [O-EIMs] are known complications of Crohn's disease [CD], ulcerative colitis [UC], and inflammatory bowel disease unclassified [IBD-U]. However, data on their prevalence in children are scarce and there are no clear recommendations on what follow-up should be offered. We aimed to review available data on O-EIMs in children. Methods: In January 2018, we performed a systematic review of published English literature using PubMed and EMBASE databases and disease-specific queries. Results: Fifteen studies [7467 patients] reported data on O-EIMs prevalence in children. Overall prevalence of O-EIMs was 0.62-1.82%. Uveitis was the most common O-EIM. Meta-analysis showed that children with CD are at increased risk of O-EIMs as compared with children with UC and IBD-U (odds ratio [OR] 2.70, 95% confidence interval [CI] 1.51-4.83). Five studies [357 patients] reported data on ophthalmological screening in asymptomatic children: mild asymptomatic uveitis was identified in a variable proportion of patients [1.06-23.1%], more frequently in male patients with CD and colonic involvement. No evidence of ocular complications from untreated uveitis was detected. A total of 23 case reports [24 patients] were identified. Conclusions: Data on O-EIMs in children are scarce. Prevalence of O-EIMs is lower than in adults but may be underestimated because of the possibility of asymptomatic uveitis; however, the long-term significance of this condition is unknown. Children with CD may be at increased risk of O-EIMs. No recommendations on routine ophthalmological examination can be made, but a low threshold for ophthalmological referral should be maintained. Larger studies in paediatric IBD populations are needed.
Keywords: Adolescent; Cataract; Child; Child, Preschool; Colitis, Ulcerative; Crohn Disease; Eye Diseases; Humans; Prevalence; Uveitis